SIRE EFFECT ON CARCASS TRAITS OF JAPANESE BROWN COW - A. B, SRI RACHMA. (Majalah Ilmiah Peternakan, 2012)
SUMMARY The present research aims to obtain more fundamental knowledge of genetic effect (sire effect) on carcass traits of the Japanese Brown cow. This experiment was done at Kumamoto Prefecture, Japan. The field data of ultrasonic estimates of carcass traits of 9468 heads of Japanese Brown cows, which were born from January 3rd 1988 to December 25th 1993, representing 88 heads of sire were collected. All data was included of pedigree status. Cows data of ultrasonic estimates of carcass traits was taken at the first registration examination (?d15 months of age or ?T 40 months of age). The carcass traits were estimated by ultrasound were Musculus longissimus thoracis area (MLTA) between the 6th and 7th ribs on the left side of each animal, Subcutaneous Fat Thickness (SFT), Intermuscular Fat Thickness (IMFT), Rib Thickness (RT) and Marbling Score (MS). The data obtained was statistically analyzed by the LSMLMW procedure and the Duncan test. The average age of cows in this study was 22.7 months. The mean of MLTA was 32.4 cm2 while the means of SFT, IMFT and RT were 10.5 mm, 18.3 mm and 44.9 mm, respectively. The mean of MS was 0.52. Sire effects were significant for all ultrasonic estimates of carcass traits (P<0.01). Cows sired by Mitsushige ET, Mitsutake, Mitsumaru, Dai 5 Harutama, Dai 10 Mitsumaru and Namimaru tended to have large MLTA, high MS and optimum SFT, IMFT and RT compared to other sires. Mitsushige ET had the highest genetic quality and might be considered as a breeding sire in selection.